Soft computing in absorption cooling systems - Kalogirou, Soteris A.; Sahin, Arzu Sencan (My University, 2011)
Absorption cooling systems make sense in many applications for process water cooling. Instead of mechanically compressing a refrigerant gas, as in the conventional vapor compression process, absorption cooling uses a thermo-chemical process. Two different fluids are used, a refrigerant and an absorbent. Heat directly from natural gas combustion, solar energy, waste-heat source or indirectly from a boiler, drives the process. In recent years, soft computing (SC) methods have been widely utilized in the analysis of absorption cooling systems. Soft computing is becoming useful as an alternate approach to conventional techniques. Soft computing differs from conventional (hard) computing in that, unlike hard computing, it is tolerant of imprecision, uncertainty, partial truth, and approximation. In this chapter, the research of applying soft computing methods for absorption cooling applications is presented
Keywords: Soft computing; Solar energy